(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Mouth ulcers is the most common problem. Clinically the lesions are single or multiple and are associated with microbial infections. This study focused to describe about the various herbal drugs for treatment of Mouth ulcer (or) Recurrent Aphthous stomatitis. The plants such as Sida cordifolia, Alchemilla vulgaris L. Vitex negundo are discussed which includes the plant profile, phytochemicals and pharmacological activity. Vitex negundo shows best activity among two plants.